Diseño de la ruta turística de agua dulce en el cantón Buena Fe provincia de Los Ríos, año 2020 - Crespo Rodríguez, Eddy Jonathan (2020)
The present research work was carried out in the province of Los Ríos, Buena Fe canton, with the general objective of designing the freshwater tourist route, following the Manual of Tourist Attractions established by the Ministry of Tourism in the year 2018. In order to create and innovate the tourist market in the canton, the freshwater route was developed. For the development of the research project, three specific objectives were established, which were achieved through various research methods. The first one allowed to identify the natural attractions of fresh water that exist in the county of Buena Fe by means of the cards for the survey and hierarchization of tourist attractions, such results allowed to give step to the selection of the attractions that will be included and developed in the route of fresh water. Was carried out through surveys with structured questions directed to the economically active population of Buena Fe, evidencing a great acceptance of the proposal of the design of the tourist route of fresh water. For the design, 6 attractions were selected, the extension of the fresh water route is 42km, in addition a map was elaborated tracing the potential route, with its respective legend and each one of the attractions to visit. The Buena Fe Fresh Water Route was elaborated, with its respective iconography, tourist package, cost profile, balance point and production cost. In conclusion, it was determined that the fresh water route would provide a great contribution to the tourism of Buena Fe and its surrounding sectors, potentializing, promoting, generating economic income and improving the tourist infrastructure of the whole canton, attracting visits from local, provincial and national tourists and positioning the product in the market. Keywords: tourist route, tourist packages, natural attractions The present research work was carried out in the province of Los Ríos, Buena Fe canton, with the general objective of designing the freshwater tourist route, following the Manual of Tourist Attractions established by the Ministry of Tourism in the year 2018. In order to create and innovate the tourist market in the canton, the freshwater route was developed. For the development of the research project, three specific objectives were established, which were achieved through various research methods. The first one allowed to identify the natural attractions of fresh water that exist in the county of Buena Fe by means of the cards for the survey and hierarchization of tourist attractions, such results allowed to give step to the selection of the attractions that will be included and developed in the route of fresh water. Was carried out through surveys with structured questions directed to the economically active population of Buena Fe, evidencing a great acceptance of the proposal of the design of the tourist route of fresh water. For the design, 6 attractions were selected, the extension of the fresh water route is 42km, in addition a map was elaborated tracing the potential route, with its respective legend and each one of the attractions to visit. The Buena Fe Fresh Water Route was elaborated, with its respective iconography, tourist package, cost profile, balance point and production cost. In conclusion, it was determined that the fresh water route would provide a great contribution to the tourism of Buena Fe and its surrounding sectors, potentializing, promoting, generating economic income and improving the tourist infrastructure of the whole canton, attracting visits from local, provincial and national tourists and positioning the product in the market. Keywords: tourist route, tourist packages, natural attractions